If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 32 = 3y + 2 Reorder the terms: 32 = 2 + 3y Solving 32 = 2 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 32 + -3y = 2 + 3y + -3y Combine like terms: 3y + -3y = 0 32 + -3y = 2 + 0 32 + -3y = 2 Add '-32' to each side of the equation. 32 + -32 + -3y = 2 + -32 Combine like terms: 32 + -32 = 0 0 + -3y = 2 + -32 -3y = 2 + -32 Combine like terms: 2 + -32 = -30 -3y = -30 Divide each side by '-3'. y = 10 Simplifying y = 10
| 3x-1=170 | | 22x=4 | | x^2-4x+y=0 | | 20-k=8 | | 3m+1=21 | | 138-3x=24x+18 | | 15=24-3x | | x^3-10x^2+21x-30=0 | | 3y-10x-22=15x-4y+31 | | 3x+114=9x-12 | | 133-2x=34x+17 | | (3z-4)(6+z)=0 | | 6x+8=-122-9x | | 183-2x=43x+23 | | 9-10x=209-45x | | 2x+3(x-5)=5(2x-3) | | 2mn+9mp= | | 4(x+3)-7x=6 | | 10-3x+8=30+2x+48 | | 17x+8=42 | | 9x-6-5x=8+x-14 | | 56-6x=3x+21 | | 5-7x=3x+21 | | -70-9x=43-21x | | (5y-2)=52 | | 14-8x+6-5x=10+2x-5 | | 6x+18=116-6x | | (x+2)(2-x)=6x-x | | 2x+36=21x-36 | | 17-6x=4x-8 | | 9-5k+2k=k-23 | | x^2+4x-1=9x-5 |